A Program Manager's Guide for Program Improvement in Ongoing Psychological Health and Traumatic Brain Injury Programs The RAND Toolkit, Volume 4 - Ryan, Gery W. (RAND Corporation, 2014)
The RAND Program Manager's Guide is a tool to help assess program performance, consider options for improvement, implement solutions, then assess how well the changes worked, with the intention of helping those responsible for managing or implementing programs. Specifically, the tool is intended to provide practical guidance in program improvement and continuous quality improvement for all programs.